Proposição de um processo de gestão de mudança como suporte para implementação de um programa corporativo de ferramentas de gestão e de melhoria contínua - Bittencourt, Alexandre Gonçalves (Universidade do Vale do Rio dos Sinos, 2017)
Organizations are continually seeking new ways to differentiate themselves through the excellence of their products and services. To do so, they should be able to select the best set of activities and projects to achieve this differentiation. It is very unlikely that organizations will carry out their projects without generating behavioral or cultural changes. However, organizations have historically faced great difficulties to implement these changes, and the literature reports significant failure rates directly linked to leadership and change management issues. This dissertation has as objective to propose a change management process to support Carrier Transicold Brazil in the implementation of a global corporate strategic management practices and continuous improvement system. In order to fulfill the objective, an action research method was used being this method a strategy that allows the researcher to develop the conceptual and analytical elements from the data collected and not from structured techniques. It is qualitative in nature, with a relation between theory and practice for the problem resolution. It has a focus on building theory for use in practice. The structure of this proposal was based on the identification of the challenges, barriers and facilitating elements in the management of organizational changes, continuing with a selection within the literature of a model of change management process adhering to the company culture. Then the change process is applied and the respective results evaluation is done in relation to the corporate strategic management practices and continuous improvement system. The robustness of the proposed and applied change management process together with the strong leadership sponsorship and the engagement of the employees involved in the process, lead to the evidence that the research objectives have been achieved. The challenge becomes to sustain the program in order reach the corporate objective.
Keywords: Gestão de mudanças; Gerenciamento de processo; Melhoria contínua; Gestão estratégica; Change management; Process management; Continuous improvement; Strategic management; ACCNPQ::Ciências Sociais Aplicadas::Administração